Peran Fasilitator Pendamping Terhadap Pengembangan Usaha Nasabah Prasejahtera BTPN Syariah - Sela Gita Dewi Paramita; Eni Setyowati (Universitas Muhammadiyah Surakarta, 2024)
The Certified Independent Study and Internship Program (MSIB) is part of the Independent Campus Learning (MBKM) policy by the Ministry of Education, Culture, Research and Technology (Kemendikbudristek). PT. Bank BTPN Syariah TBK is one of the partners of the MSIB Batch 5 program. Bank BTPN Syariah provides intermediaries as accompanying facilitators to support customers in achieving their expected goals. The role of the companion here is to help customers maximize sales. BTPN Syariah customers as ultra-micro actors receive facilities in the form of companions so they can help them in developing their business. The accompanying facilitators provided by Bank BTPN Syariah have the aim of supporting BTPN Syariah customer empowerment activities, especially women/mothers from productive underprivileged communities or micro business actors, who have the capacity and skills along with customer skills in running their businesses, so that they can develop more and opening wider market access, both offline and online.